2015
DOI: 10.1007/s00381-015-2837-9
|View full text |Cite
|
Sign up to set email alerts
|

ICP monitoring in children: why are we not adhering to guidelines?

Abstract: Our study confirms that many children with severe TBI do not undergo ICP monitoring, mainly due to rapid improvement or moribund status. A subgroup of patients, with reassuring cerebral CT scan, was not monitored. Further research is necessary to assess if imaging should be considered in ICP indication, as in adult guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Notably, ICP monitoring in this study was associated with decreased mortality only when the GCS was 3 but was associated with longer ICU stay, longer hospitalization, and more days on the ventilator, potentially reflecting the population most likely to be chosen to undergo monitoring [39]. In the past decade, reported rates of ICP monitoring in the pediatric population have ranged from 7.7 to 59 % [39][40][41][42][43]. It has been shown that infants less than 1 year are less likely to undergo ICP monitoring [41,42] than are older children.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…Notably, ICP monitoring in this study was associated with decreased mortality only when the GCS was 3 but was associated with longer ICU stay, longer hospitalization, and more days on the ventilator, potentially reflecting the population most likely to be chosen to undergo monitoring [39]. In the past decade, reported rates of ICP monitoring in the pediatric population have ranged from 7.7 to 59 % [39][40][41][42][43]. It has been shown that infants less than 1 year are less likely to undergo ICP monitoring [41,42] than are older children.…”
Section: Introductionmentioning
confidence: 77%
“…In the past decade, reported rates of ICP monitoring in the pediatric population have ranged from 7.7 to 59 % [39][40][41][42][43]. It has been shown that infants less than 1 year are less likely to undergo ICP monitoring [41,42] than are older children. Additionally, children hospitalized at adult-only trauma centers are more likely to have ICP monitors placed than are pediatric patients cared for at pediatric trauma centers [41].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…10 The decision not to monitor ICP often depends on analysis of clinical risks and potential benefits; it may be considered too invasive and risky in patients with improving Glasgow Coma Scale scores, and futile in moribund patients with catastrophic brain injuries. 16 The method that we present here may provide an alternative that allows for more frequent use of ICP monitoring to screen for and help in the management of elevated ICP in very young patients.…”
Section: Resultsmentioning
confidence: 99%